Transcatheter Embolization in Congenital Cardiovascular Malformations-Variable Use of Vascular Plugs - Jochen Pfeifer; Anas Gheibeh; Peter Fries; Martin Poryo; Axel Rentzsch; Hashim Abdul-Khaliq (Hindawi-Wiley, 2024)
Conclusion: Embolization using AVP is a suitable approach for closure of various cardiovascular malformations with a high primary success rate and low complication rate. It should be considered in treatment of different irregular vessel anomalies and in selected VSD.